O projeto pedagógico e a autonomia da escola - Vieira, Elisangela Gama Mamedio (2010)
This work deals with the School Management with emphasis on participatory planning, based on the search for appropriate understanding about the Pedagogical Project (PP), to encourage the autonomy and pedagogical development of the school. Therefore the search arises this need for a deepening theoretical on design, purpose and benefits of PP, as well as the importance of their preparation with the participation of all the school community. Thinking have a result exitoso this research the theoretical focus is in the area, but especially Paulo Freire, seeking authors reference point to the question of the construction and use of pp a strong tool for ensuring the autonomy and monitoring of procedural planning the medium and long term of the school, whereas the premise of a planning with the participation the school community. This work will also be based on documents proposed by the MEC, as the Law of Directives and National Education Bases LDB, No 9394/96, in addition to the documents underlying the propositions of the Council for Education.